HIGH-EFFICIENCY INSTALLATION SYSTEM USING DISTRIBUTION TYPE FULFILLMENT - KWON MIN KOO; AHN MICHAEL (2022)
The present invention provides a high-efficiency product installation system using distribution type fulfillment, which comprises: a collection unit which receives, exchanges, and stores a product from a sales unit; a first distribution unit for performing first distribution from the collection unit; a second distribution unit for performing second distribution of the product after the completion of the first distribution unit; a third distribution unit for performing third distribution of the product after the completion of the second distribution of the second distribution unit; and a fourth distribution unit for completing the delivery and installation of the product. According to the present invention, a time and costs required for the delivery and installation of the product can be significantly reduced to maximize delivery efficiency, and a movement path of a delivery subject can be uniformized, simplified and patterned in a process of delivery of the product, thereby minimizing fatigue and a movement distance. In addition, even when there are rapid changes in volume of products transported, flexible response can be possible. 본 발명은 판매부로부터 물품을 수령, 교환 및 보관하는 수집부, 수집부로부터 제1 분배를 실시하는 제1 분배부, 제1 분배부의 완료 후 물품의 제2 분배를 실시하는 제2 분배부, 제2 분배부의 제2 분배 완료 후 물품의 제3 분배를 실시하는 제3 분배부 및 물품의 배송과 설치를 완료하는 제4 분배부를 포함한다. 본 발명에 따르면, 물품의 배송 및 설치에 소요되는 시간 및 비용을 획기적으로 단축할 수 있어 배송 효율을 극대화할 수 있고, 물품의 배송 과정에서 배달 주체의 이동 경로를 획일화, 간소화 및 패턴화할 수 있어 피로도 및 이동 거리를 최소화할 수 있으며, 물동량이 급격히 변화하더라도 탄력적으로 대응 가능한 효과를 갖는다.